Reducing the burden of road traffic injury: translating high-income country interventions to middle-income and low-income countries. - Stevenson, M.; Yu, J.; Hendrie, Delia; Li, L.; Ivers, R.; Zhou, Y.; Su, S.; Norton, R. (BMJ Publishing Group, 2008)
Objective: To increase seat belt restraint use in Guangzhou City, People’s Republic of China. Design: Comparison group pre-test, post-test design. Setting: Guangzhou City. Interventions: Interventions to increase the prevalence of seat belt use in high-income countries (enhanced training and enforcement practices along with raising of public awareness) were adapted and implemented in Guangzhou. The prevalence of seat belt use was determined before and after the introduction of the 12-month intervention. Seat belt prevalence was also examined over the same time period in the neighboring city of Nanning, and an incremental cost-effectiveness analysis of the intervention was undertaken. Main outcome measures: Prevalence rates and incremental cost effectiveness ratios. Results: A 12% increase in seat belt use was observed in Guangzhou over the study period, increasing from a prevalence of 50% before (error range 30–62%) to 62% after (error range 60–67%) (p<0.001) the intervention; an absolute change difference between the intervention and reference city of 20% was achieved. The incremental cost-effectiveness ratio of the intervention was ¥3246 (US$418) per disability-adjusted life year saved. Conclusions: This city-wide intervention demonstrates that it is possible to increase the prevalence of seat belt use using similar methods to those used in high-income countries and, importantly, that such an approach is cost-effective.